2012
DOI: 10.4028/www.scientific.net/amr.445.560
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Friction Stir Processing with Internally Cooled Tool

Abstract: Friction stir processing (FSP) is considered to be a promising sustainable technique for grain refinement of metallic alloys. The heat generated during FSP promotes dynamic recrystallization in processed material which is essential for grain sub-division process. However, excessive heat generation can lead to high temperatures of >300°C that may cause abnormal grain growth in the processed material. On the other hand, repetitive high temperature heating cycles can reduce the lifetime of the FSP tool. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…CFD analysis of FSP is carried out to study the effects of processing parameters, such as tool rotational and translational speeds, on temperature fields, flow stresses, and microstructure evolution. For the sake of brevity, the discussion here will be limited to grain size prediction, more details can be found at [6]. The average recrystallized grain size in stirred and transition zones of the processed sheet is evaluated from temperature and strain rate fields using Zener-Holloman relation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD analysis of FSP is carried out to study the effects of processing parameters, such as tool rotational and translational speeds, on temperature fields, flow stresses, and microstructure evolution. For the sake of brevity, the discussion here will be limited to grain size prediction, more details can be found at [6]. The average recrystallized grain size in stirred and transition zones of the processed sheet is evaluated from temperature and strain rate fields using Zener-Holloman relation.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this model is to predict the grain size after processing, starting from the as received microstructure. More details about the model can be found in [6]. In this model the sheet is assumed to behave as a non-Newtonian highly-viscous fluid.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The authors found that the microstructures of all the samples were characterized by fine equiaxed grains in the stirring zone, but the greatest elongation of the samples was achieved for the CO 2 -cooled sample due to the lowest heat input during FSP. In turn, in [32], friction stir processing of the AZ31B magnesium alloy was performed using an internally cooled FSP tool. The authors found that the applied solution allowed effective temperature control during processing, which leads to improvement of the mechanical properties through effective grain refinement and has a positive effect on the tool life.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the microstructures of all the samples were characterized by ne equiaxed grains in the stirring zone, but the greatest elongation of the samples was achieved for the CO 2 cooled sample due to the lowest heat input during FSP. In turn, in [32] friction stir processing of the AZ31B magnesium alloy was performed using an internally cooled FSP tool. The authors found that the applied solution allowed effective temperature control during processing, which leads to improvement of the mechanical properties through effective grain re nement and has a positive effect on the tool life.…”
Section: Introductionmentioning
confidence: 99%